Changes in incisors and their relationship with point A and nasolabial angle in Class II division 2 patients treated with and without extractions at the UPCH Teaching Dental Center. - Meneses, Abraham (2022)
Background: There are studies evaluating cephalometric parameters in Class II division 2 patients. There are no similar investigations in Peru. Objective: To evaluate post-treatment changes in incisor inclination and position and their relationship with the nasolabial angle (ANL) and point A (PA) in Class II division 2 patients, with and without extractions in cases of the Orthodontic specialty program of the Universidad Peruana Cayetano Heredia. Material and methods: manual tracing and measurements of 62 lateral cephalometric radiographs (31 pre and 31 post-treatment) were performed, of patients with Malocclusion Class II division 2. Statistical analysis was performed with SPSS 21.0 for Windows. Results: There was proinclination and incisive protrusion in all patients. In patients with extractions, the ANL presented non-significant changes, but significant correlations: when the lower incisor inclination increased, the ANL decreased; when ANL increased, the interincisal angle (AII) increased. Point A (PA) experienced changes and correlations, but not significant. In patients without extractions, no correlations or significant changes were found in BP or ANL. Women treated without extraction did not show significant changes, in men the most significant changes were lower incisor inclination and protrusion. In the cases with extractions in men it was AII; and in women the AII and the upper incisor angle / palatal plane. Conclusions: There is a relationship between the changes that occur in the incisors and the ANL and PA, although most are not statistically significant.